Event-Related Potential Evidence for Involuntary Consciousness During Implicit Memory Retrieval - Liang, Xiu-Yuan; Guo, Zi-Hao; Wang, Xiao-Dong; Guo, Xiao-Tao; Sun, Jing-Wu; Wang, Ming; Li, Hua-Wei; Chen, Lin (Frontiers in Behavioral Neuroscience, 2022)
Classical notion claims that a memory is implicit if has nothing to do with consciousness during the information retrieval from storage, or is otherwise explicit. Here, we demonstrate event-related potential evidence for involuntary consciousness during implicit memory retrieval. We designed a passive oddball paradigm for retrieval of implicit memory in which an auditory stream of Shepard tones with musical pitch interval contrasts were delivered to the subjects. These contrasts evoked a mismatch negativity response, which is an event-related potential and a neural marker of implicit memory, in the subjects with long-term musical training, but not in the subjects without. Notably, this response was followed by a salient P3 component which implies involvement of involuntary consciousness in the implicit memory retrieval. Finally, source analysis of the P3 revealed moving dipoles from the frontal lobe to the insula, a brain region closely related to conscious attention. Our study presents a case of involvement of involuntary consciousness in the implicit memory retrieval and suggests a potential challenge to the classical definition of implicit memory.